Correlation Between Periodontal Pocket Depth And Periodontal Disease In Down Syndrome Considering Age, Sex, Nutrition, Toothbrushing - Naifatul Aulia Ahmad; Nuryanni Dihin Utami; Nydia Hanan; Sinar Yani; Listiyawati Listiyawati (Jurnal Medali, 2026)
Background: Down syndrome is a genetic disorder with a high prevalence of periodontal disease. Increased periodontal pocket depth is one of the important indicators in assessing periodontal tissue damage. Factors such as age, sex, nutritional status, and toothbrushing practice are thought to influence periodontal conditions in individuals with Down syndrome. This study aims to analyze the relationship between these factors and periodontal pocket depth values in individuals with Down syndrome.Method: This study used an analytical observational design with a cross-sectional approach involving 40 respondents who met the inclusion criteria. Clinical examination of periodontal pocket depth was carried out using a WHO probe at six points of each tooth. Nutritional status data were obtained through body mass index (BMI) measurements, while toothbrushing practice and respondent characteristics were obtained through structured interviews. Data analysis included Spearman and Chi-square tests with a significance level of p<0,05.Result: The results showed a significant relationship between age (p=0.000; r=0.646) and toothbrushing practice (p=0.008; r=0.412) with periodontal pocket depth. Meanwhile, sex (p=0.726) and nutritional status (p=0.679) did not show a significant relationship with periodontal pocket depth in individuals with Down syndrome.Conclusion: The results showed a significant relationship between age (p=0.000; r=0.646) and toothbrushing practice (p=0.008; r=0.412) with periodontal pocket depth. Meanwhile, sex (p=0.726) and nutritional status (p=0.679) did not show a significant relationship with periodontal pocket depth in individuals with Down syndrome